2007
DOI: 10.1152/ajpheart.00306.2007
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen increases smooth muscle expression of α2C-adrenoceptors and cold-induced constriction of cutaneous arteries

Abstract: Raynaud's phenomenon, which is characterized by intense cold-induced constriction of cutaneous arteries, is more common in women compared with men. Cold-induced constriction is mediated in part by enhanced activity of alpha(2C)-adrenoceptors (alpha(2C)-ARs) located on vascular smooth muscle cells (VSMs). Experiments were therefore performed to determine whether 17beta-estradiol regulates alpha(2C)-AR expression and function in cutaneous VSMs. 17beta-Estradiol (0.01-10 nmol/l) increased expression of the alpha(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 53 publications
2
78
1
3
Order By: Relevance
“…25 Recently, it was reported that expression of the adrenergic 2C-receptor is enhanced by estrogen. 26 Although it was seen in cutaneous arterioles in vivo, estrogen may enhance the expression of adrenergic 2C receptor in deep arteries, which in females showed less expansion against cold exposure in the present study.…”
Section: Sex Difference In the Vascular Response To Cold Exposurecontrasting
confidence: 54%
“…25 Recently, it was reported that expression of the adrenergic 2C-receptor is enhanced by estrogen. 26 Although it was seen in cutaneous arterioles in vivo, estrogen may enhance the expression of adrenergic 2C receptor in deep arteries, which in females showed less expansion against cold exposure in the present study.…”
Section: Sex Difference In the Vascular Response To Cold Exposurecontrasting
confidence: 54%
“…This may reflect the influence of estrogen in the prevalence of RP, higher in women than in men, and decreasing in postmenopausal women. Of interest, a recent study (9) has shown that estrogen can increase the expression of ␣ 2C -adrenoreceptors and also increased ␣ 2 -adrenoreceptor-mediated constriction during exposure to cold. In the present study, we were not able to observe any difference between women according to their hormonal status, but the sample size was too small to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Eid et al (5) reported that the treatment of 17␤-estradiol on human cultured vascular muscle cells interacted with cell surface receptors to cause an increase in ␣ 2C -adrenoceptor transcription. Thus, the activation of the vestibulosympathetic reflex may elicit differences in vascular transduction at times of low and high estrogen due to the expression of postsynaptic ␣ 2 -adrenoceptors on the smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%